Global Surge in Intimate Partner Violence after Mandatory Lockdown: Implications for Pakistan - Butool Hisam; Mohammad Nadir Haider; Ghazala Saleem (Journal of the Pakistan Medical Association, 2021)
We are observing with great concern the global spread of the COVID19 Pandemic. What is equally alarming is a less visible, albeit serious Public health issue; one that the United Nations has dubbed as the ‘Shadow Pandemic’ [1]. This is none other than the globally prevalent issue of violence against women, particularly Intimate Partner Violence. Intimate Partner Violence (IPV) is a serious, possibly preventable public health problem globally. Pakistan ranks among the countries with the highest IPV rates [2]. On 11th March 2020, the World Health Organization declared the highly infectious and lethal Severe Acute Respiratory Syndrome Coronavirus 2 (COVID-19) to be a pandemic [3]. Drastic measures were enforced universally to curb the spread of COVID-19. Countries issued strict nationwide lockdowns to isolate the population and implemented social distancing. The economy was impacted tremendously, and many people experienced financial and emotional hardship during this mandatory confinement. While everyone was affected, one population was in a far worse situation than others. Survivors of IPV were trapped alongside their perpetrators and faced difficulty/less freedom to escape threatening situations compared to the past. It is not surprising given that historical periods of uncertainty such as war or economic crisis have resulted in increased interpersonal violence, including violence against women [4]. The Hubei province of China, the first region to undergo a lockdown, saw nearly a doubling of their rates of IPV with the start of COVID19 Pandemic. Similarly, tragic stories gained nationwide coverage in the United States. IPV may also have risen in Pakistan, even if it is not being covered as extensively. During pandemics, fear causes us to minimize our personal needs and make sacrifices we would not normally make. This could be a reasonable approach for most but should not be for survivors of IPV. IPV survivors live in constant fear for themselves and their children; they are now devoid of their only means of mitigation; avoidance. Local woman’s support groups in Pakistan should act and spread awareness about this grim reality hiding underneath the Pandemic. Resources/funding should be made available for survivors to be able to reach out for support without having to leave the watchful eyes of their perpetrators. Public health officials ought to investigate and document the rise in IPV to help identify the leading causes of the increase. These steps will assist in developing crisis-specific guidelines to provide adequate resources for the future. Continuous....